Pemanfaatan Remitansi Pekerja Migran Indonesia Serta Peran Usaha Pekerja Migran Indonesia Purna Untuk Pembangunan Desa Asal - Bothy Dewandaru; Afif Nur Rahmadi; Evi Husniati Sya’idah (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2019)
The program to send migrant workers abroad was chosen because of the assumption that working abroad as migrant workers has a higher income than work in Indonesia. The large number of migrant workers will have an impact on the number of remittances sent to families, forms of remittance not only in money but also in the form of goods, and knowledge. This study aims to determine the use of remittances in Deyeng Village, Kediri Regency and the role of post-migrant workers. This study is a qualitative research data source obtained from interviews, questionnaires, observations and Focus Group Discussion (FGD), the informants selected from prosperous TKM cooperative members who are retired migrant workers and migrant workers' families as many as 40 people. The results showed that the use of remittances was more for consumptive needs which consisted of basic needs, home renovation, transportation equipment, electronic equipment, and debt repayment compared to productive needs such as buying land, kept in banks, business capital, buying livestock, and children's education. The role of ex-migrant workers is not maximal because training and assistance from the Manpower Office have not shown maximum results.